Radix Tetrastigma Inhibits the Non-Small Cell Lung Cancer via Bax/Bcl-2/Caspase-9/Caspase-3 Pathway. (2nd January 2022) - Li, Yonglu; Wang, Yaxuan; Yu, Xin; Yu, Ting; Zheng, Xiaodong; Chu, Qiang
Abstract: Lung cancer with high mortality is regarded as a challenging global problem with unsatisfied curative effects. Clinically, the chemotherapy drugs are often faced with side-effects and tumor resistance. Radix Tetrastigma (RT) is a traditional Chinese herb and now regarded as a kind of functional food. In this study, A549-bearing nude mice control was adopted to evaluate the anti-tumor capacity of RT. Results demonstrated that RT showed excellent anti-tumor ability with no side-effect on mice compared to chemotherapy drug (5-Fu).Further studies proved that RT down-regulated the proliferation-related proteins (PCNA, Ki67) and vascular endothelial growth factor (VEGF). Additionally, RT up-regulated the ratio of Bax/Bcl-2, which caused the over-expression of Caspase-9, leading to the activation of downstream protein caspase-3, eventually resulting in apoptosis of A549 in solid tumor. These results together suggest that RT inhibits the non-small cell lung cancer (NSCLC) via Bax/Bcl2/Caspase-9/Caspase-3 pathway. Furthermore, the anti-A549 abilities of the main flavonoid components from RT were compared, and kaempferol-3-O-rutinoside would play a role in RT's outstanding anti-NSCLC ability.